Physical therapy of static and dynamic motor disorders in children with hemiplegic cerebral palsy - Oleh Nekhanevych; Yun Byoung-Yul (Kazimierz Wielki University, 2020)
Introduction Regardless an improgressive habit of neural disorders in cerebral palsy (CP), without a therapy the motor abnormalities' severity rising is registered and as a result with age the physical dysfunction progressively increases. Purpose To improve the static and dynamic motor disorders' and activity limitations physiotherapy efficiency among the children with hemiplegic CP form via the therapeutic training program on the developed device for rehabilitation of the people with muscle-skeleton disorder. Material and methods 24 children with unilateral CP aged from 6 to 11 were enrolled into the research. The patients were randomized into 2 groups. Additionally to the standard physiotherapy complex the I group were prescribed with the walking trainings on the rehabilitation device according to the dynamic method, the II group - according to the static method. Physiotherapy program duration was 6 weeks. The gait spatiotemporal characteristics and activity limitations were monitored. Results Appling developed program influenced on the walking spatiotemporal indexes in the both groups. The biggest increase of the distance and stride length were reached exactly on the 2  week. Herewith, distance incremental amount in the I group was higher than in the II study group. TUG test's time decreased statistically efficiently in the I group. Maximum TUG test's index depression was observed on the 6th study weeks. As a result GMFM-66 increased in I group. Conclusions             An administration of the developed therapeutic program affected positively on the CP patients' spatiotemporal walking characteristics, balance and endurance, as a result, decreased the fall risk and activity limitations.